An Alternative Approach to the Fracture Toughness of Dual Phase Steels - Ulu, S.; Aytekin, H.; Said, G. (Проблемы прочности, 2013)
In this study, the effects of ferrite morphology and of ferrite volume fraction on the mechanical properties and the fracture toughness values ( ) KIc of dual phase steels were investigated. The fracture toughness values were determined using an approach that was different from the standard one. A homogenization heat treatment was applied to the steels. Two different starting microstructures were then obtained by either the full annealing of or the quenching of the steels from austenite before applying intercritical annealing to the steels in the austenite region. After this process, dual phase steels with two types of morphology, coarse and fine, were obtained with 40, 20, and 10% ferrite volume fractions, depending on the starting microstructure. Tempered specimens with 10% ferrite exhibited improved fracture toughness values compared with those of the other steels.